Synergistic Integration of Carbon Quantum Dots in Biopolymer Matrices: An Overview of Current Advancements in Antioxidant and Antimicrobial Active Packaging - Singh, Ajit Kumar; Itkor, Pontree; Lee, Myungho; Saenjaiban, Aphisit; Lee, Youn Suk (Molecules (Basel, Switzerland), 2024)
Approximately one-third of the world’s food production, i.e., 1.43 billion tons, is wasted annually, resulting in economic losses of nearly USD 940 billion and undermining food system sustainability. This waste depletes resources, contributes to greenhouse gas emissions, and negatively affects food security and prices. Although traditional packaging preserves food quality, it cannot satisfy the demands of extended shelf life, safety, and sustainability. Consequently, active packaging using biopolymer matrices containing antioxidants and antimicrobials is a promising solution. This review examines the current advancements in the integration of carbon quantum dots (CQDs) into biopolymer-based active packaging, focusing on their antioxidant and antimicrobial properties. CQDs provide unique advantages over traditional nanoparticles and natural compounds, including high biocompatibility, tunable surface functionality, and environmental sustainability. This review explores the mechanisms through which CQDs impart antioxidant and antimicrobial activities, their synthesis methods, and their functionalization to optimize the efficacy of biopolymer matrices. Recent studies have highlighted that CQD-enhanced biopolymers maintain biodegradability with enhanced antioxidant and antimicrobial functions. Additionally, potential challenges, such as toxicity, regulatory considerations, and scalability are discussed, offering insights into future research directions and industrial applications. This review demonstrates the potential of CQD-incorporated biopolymer matrices to transform active packaging, aligning with sustainability goals and advancing food preservation technologies.